A Preliminary Report on The Syntheses of Oligonucleotide Primers in The National Research and Innovation Agency (NRIA) - Atikana, Akhirta; Prasetyoputri, Anggia; Rubiyana, Yana; Herawati, Neng; Desriani, Desriani; Pratiwi, Riyona Desvy; Wulandari, Dwi; Sukmarini, Linda; Kusharyoto, Wien; Santoso, Adi; Putra, Masteria Yunovilsa; Lisdiyanti, Puspita (Annales Bogorienses, 2022)
A PolyGen DNA Synthesizer is equipment that is used for synthesizing oligonucleotide primers for any amplification targets. Oligonucleotide primers are indispensable components for any Polymerase Chain Reaction (PCR)-based detections. In the present study a number of oligonucleotide primer sets were synthesized to target (1) the Human Insuline Glargin (HIG) and (2) the Human Erythropoietin (EPO), as well as (3) the RNA-dependent RNA Polymerase (RdRp) and (4) the Nucleocapsid (N) genes of the severe acute respiratory syndrome virus 2 (SARS-CoV-2). A solid-phase oligonucleotide synthesis method was used according to the default protocol of the Polygen’s instrument to synthesize primers at a 40 nmol scale. The synthesized primers in this study were compared to commercially produced primers in their ability to amplify the gene target(s) in PCR and quantitative real-time PCR (qPCR) reactions. The first two sets of primers showed similar results in PCR compared to commercial primers; however, these primers were not tested for qPCR due to sample limitation. In contrast, the primer sets 3 and 4 were not able to produce amplicons in PCR reactions and only the primer set 4 successfully amplified the gene target in qPCR. These results indicate that the crude primers synthesized in this study are promising candidates for molecular detection and diagnostics, but these primers would benefit from further optimization for routine applications.